Archetypes & Self-Realization in Disney's Cruella (2021) Movie: Jungian Psychoanalysis - Fatihah, Nadyatul; Mustofa, Ali (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2022)
The research focused on archetypal elements in the Disney film Cruella. The goal was to see how Estella's personality reflected Jung's archetype theory. Carl Gustav Jung identified the major archetypes, which are the result of shared ancestral experiences that can be found in art, literature, and religion but are not readily evident to the naked eye. Archetypes are inherited, universal patterns of people, actions, or personalities that have an impact on human behaviour. Watching the movie, reading the movie's transcription, selecting quotes, studying cinematographic elements, identifying the data based on the study's theme, and classifying the data to point out the issues of Jung's archetype in the movie were all used to assemble the data. According to the findings, Jung's archetypes were depicted in the film. The results of the research revealed that the main character's speech and actions reflected Jung's archetypes. According to the discussion, Estella's mental growth is obtained from three aspects: her persona, shadow, and self-realization. Self-realization is attained through breaking free from the constraints of the persona, recognizing and accepting the shadow, and balancing the two sides. Despite being difficult and perhaps dangerous, those are critical stages on the way to mental and psychic developmen